1988
DOI: 10.1177/030802268805100804
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Students for Occupational Therapy

Abstract: With the integration of St Joseph's College of Occupational Therapy into the Faculty of Health Sciences at Trinity College, Dublin, the selection procedures were reviewed to consider using academic criteria alone. The relevant literature is reviewed and the decision to select students using academic criteria alone in the majority of cases is discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This gives weight to the ideas of King (1988) and aligns with the findings of Howard and Watson (1998). It supports growing practice to encourage a rich mix among occupational therapy students and generally widen the entry gate.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This gives weight to the ideas of King (1988) and aligns with the findings of Howard and Watson (1998). It supports growing practice to encourage a rich mix among occupational therapy students and generally widen the entry gate.…”
Section: Discussionsupporting
confidence: 62%
“…Academic failure may be addressed by attention to entry requirements, although King (1988) suggests that good Advanced Level scores (A Levels) alone do not predict academic success. Academic difference between A Levels and other qualifications may be less important than the motivation implied by completion of access courses and so on.…”
Section: The Literaturementioning
confidence: 99%
“…There was a dearth of literature that was specific to therapy student selection and what was available tended to be contradictory. The perspectives ranged from academic performance solely being considered the best indicator of success on the course (Vargo et al 1986, King 1988 to advocating that multiple measures be used to predict future success (Isenberg and Heater 1994). A paper by Kerr (1985), pertaining to physiotherapy students, found that 62% of the variance of the degree was not accounted for by pre-entry factors.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, opinions vary about preferred selection methods for occupational therapy students. For example, there are claims that previous academic performance is the best predictor of student success within a program, suggestions that multiple selection methods should be used, and conclusions that there is little evidence of the superiority of any admission path into an occupational therapy program (Isenburg & Heater, 1994;King, 1988;Wheeler, 2001).…”
Section: Selectionmentioning
confidence: 99%